2011
DOI: 10.1007/s00704-011-0526-5
|View full text |Cite
|
Sign up to set email alerts
|

Relating remotely sensed forest damage data to wind data: storms Lothar (1999) and Vivian (1990) in Switzerland

Abstract: This study compares the surface wind speed and forest damage data of two exceptionally severe winter storms, Vivian 1990 and Lothar 1999. The study area comprises the region that suffered damage in Switzerland. The wind speed data were derived from simulations of MeteoSwiss (Federal Office of Meteorology and Climatology), measurements during the storm periods and expert analyses of the data. The remotely sensed forest damage data were provided by the Federal Office for the Environment and the forest cover data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 48 publications
0
9
0
Order By: Relevance
“…This reflects the extremely localised effects of variations in wind speed during a storm. Usbeck et al (2012) found that wind gust speed at the surface was the most important factor leading to damage and dominated all other factors, but found it very difficult to correlate wind speeds directly with damage to particular stands. Schütz et al (2006) and Albrecht et al (2012) also could not find a correlation between damage and measured wind speeds; this is probably a reflection of the spatial resolution of the measurements or model simulations used, and points to the extremely local variability in wind speeds during storms (Boose et al, 1994).…”
Section: Observed Damagementioning
confidence: 96%
See 2 more Smart Citations
“…This reflects the extremely localised effects of variations in wind speed during a storm. Usbeck et al (2012) found that wind gust speed at the surface was the most important factor leading to damage and dominated all other factors, but found it very difficult to correlate wind speeds directly with damage to particular stands. Schütz et al (2006) and Albrecht et al (2012) also could not find a correlation between damage and measured wind speeds; this is probably a reflection of the spatial resolution of the measurements or model simulations used, and points to the extremely local variability in wind speeds during storms (Boose et al, 1994).…”
Section: Observed Damagementioning
confidence: 96%
“…Until there are improvements in meso-scale airflow modelling (e.g. Lopes da Costa et al, 2006), accurate prediction of damage at a stand level in complex terrain remains extremely challenging (Usbeck et al, 2012). Another possible cause for the over-prediction of damage to older stands is the accuracy of available stand data for input to the models.…”
Section: Forestgales Limitationsmentioning
confidence: 98%
See 1 more Smart Citation
“…Usbeck et al, 2011 andKlaus et al, 2011). If topographic exposure is used, however, it is difficult to separate effects of hazards and exposure in climate-change impact assessments.…”
Section: Introductionmentioning
confidence: 99%
“…The high-resolution RCM run realistically reproduced observed storm features and the gusts along the cold front were often close to observations and exceeded hurricane strength. Other extratropical winter storms were investigated in RCM studies, such as Anatol (Nilsson et al 2007), Lothar and Vivian (Usbeck et al 2012), and Xynthia (Liberato et al 2013). These studies showed that an RCM with a high resolu-tion of 2 km produces a realistic wind field compared with observations.…”
Section: Introductionmentioning
confidence: 99%